Synthesis and Properties of Bionanocomposites of Polyhydroxybutyrate-Polylactic Acid Doped with Copper and Silver Nanoparticles - Galo Cárdenas-Triviño; Nelson Linares-Bermúdez; Mario Núñez-Decap (International Journal of Polymer Science)
Global pollution has caused a real interest on the use of biodegradable materials to the sustainable development. PLA and PHB are interesting materials due to their properties and their biodegradability, and their blends in different ratios are proposed in this study; also, Ag and Cu nanoparticles were incorporated to observe possible enhances and advantages on it. Blends were characterized through FTIR, TGA, tensile, and DMA tests. Theoretically, results obtained were coherent; FTIR spectra showed a characteristic band (around 1740 cm-1) corresponding to the carbonyl bond at different intensities for each blend which is an evidence of the polymers. Likewise, TGA results showed different marked decomposition points (except for PLA/PHB 70/30), which is another indicative parameter. Regarding tensile tests, PLA/PHB/nanoparticle (NP) blends showed higher Young modulus value action improving exponentially some properties and they can act as a powerful complementary component even in small amounts. The NPs incorporated exhibited clustering due to the blending process with ranges from 93.24 nm for Cu to 123.71 nm for Ag.